1991
DOI: 10.1002/1097-0142(19910601)67:11<2833::aid-cncr2820671121>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic densities and risk of breast cancer

Abstract: To determine the relation of mammographic densities to subsequent breast cancer risk, a case-control study was undertaken using prediagnostic mammograms of screening program participants. Mammograms of cases (n = 266) and controls (n = 301) were blindly assessed for mammographic densities, which were measured by planimetry. The odds of breast cancer increased steadily with increasing breast density (test for trend, P < 0.0001). Breast cancer odds was 1.7 for densities between 5% and 24.9%, 2.5 for 25% through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
116
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(132 citation statements)
references
References 15 publications
12
116
0
4
Order By: Relevance
“…It has also been found that during lactation, IGF-1 plays an important role in the maintenance of the adult mammary gland [48][49][50]. Furthermore, percent mammographic density refers to the structure of the adipose, epithelial and connective tissue in the breast [51]. Thus, the growth factors and estrogens in combination, are key factors in proliferation of breast cells and are potential drivers for breast cancer development [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that during lactation, IGF-1 plays an important role in the maintenance of the adult mammary gland [48][49][50]. Furthermore, percent mammographic density refers to the structure of the adipose, epithelial and connective tissue in the breast [51]. Thus, the growth factors and estrogens in combination, are key factors in proliferation of breast cells and are potential drivers for breast cancer development [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesised that breast size predicts a woman's risk of breast cancer because of increased breast cell numbers, and both chest size (as indicated by bra size) and breast size (as indicated by cup size) have been found to predict breast cancer (Egan et al, 1999). Breast density, a marker of cellularity of the breast, is related to breast cancer (Saftlas et al, 1991), suggesting that associations between measures of breast size and breast cancer may reflect greater numbers of breast cells leading to increased risk.…”
Section: Trunk Lengthmentioning
confidence: 99%
“…These methods have included the estimation of the percentage of mammographically detected fibro-glandular breast tissue with epithelial and connective tissue elements (as mammographic density). Harvey and Bovbjerg (2003) reviewed 12 studies reporting the association of mammographic density measured with quantitative methods to breast cancer risk (Boyd et al, 1982(Boyd et al, , 1995Brisson et al, 1982Brisson et al, , 1984Brisson et al, , 1989Wolfe et al, 1987;Saftlas et al 1991;Byrne et al, 1995;Kato et al, 1995;Van Gills et al, 1999;Lam et al, 2000;Maskarinec and Meng, 2000). All of these studies have shown moderate to strong associations of increased breast cancer risk with increased levels of mammographic density.…”
mentioning
confidence: 99%